2014
DOI: 10.2478/ijpeat-2013-0005
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Structural Analysis of Flexible Pavements Using Finite Element Method

Abstract: The evaluation of bituminous concrete mixes for their tendency to rutting has been an important research field for many years. Rutting is a major type of distress encountered in bituminous pavements. The Finite Element Method (FEM) is a numerical analysis technique to obtain various structural parameters such as stress, strain and deflection of pavement layers. The objective of this paper is to study the sensitivity of these variables in reducing the vertical surface deflections, the critical tensile strains a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…The contact area can be modeled as a circular shape or rectangular shape, and in the case when contact is modeled in rectangular shape it is guided to have a dimension of BΧ0.7B. The moving tire can be embody as an imprint area to represent a smooth pavement surface [8], [9].…”
Section: Load and Boundary Conditionmentioning
confidence: 99%
“…The contact area can be modeled as a circular shape or rectangular shape, and in the case when contact is modeled in rectangular shape it is guided to have a dimension of BΧ0.7B. The moving tire can be embody as an imprint area to represent a smooth pavement surface [8], [9].…”
Section: Load and Boundary Conditionmentioning
confidence: 99%
“…Whatever the choice, with good engineering, the road should out live its design life and serves the community well (Shere, Worku and Keno, 2018). The principal function is to receive load from the traffic and conveys it through its layer to the subgrade (Gupta, 2014). Ogundipe (2008) stated that a pavement is said to be defective when it can no longer perform this function during its design life.…”
Section: Introductionmentioning
confidence: 99%
“…This was also supported by the works of Gupta (2003) and Ajani (2006). Gupta (2014), Momoh et al (2008) and Adiat et al (2009) in their study of failed highway pavements using geophysical methods, found that some geological factors influence road failure such as the near surface geologic sequence, existence of geological structures like fractures and faults, presence of laterites, existence of ancient stream channels, and shear zones.…”
Section: Introductionmentioning
confidence: 99%
“…The major causes of failure in asphalt pavement are fatigue cracking caused by excessive vertical compressive and horizontal tensile strain at the top subgrade and bottom of asphalt layer due to repeated traffic loading and rutting deformation, caused by densification and shear deformation of sub grade. Excess vertical surface deflections in flexible pavements have always been major concern and used as a criterion of pavement design [1].…”
Section: Introductionmentioning
confidence: 99%